2016
DOI: 10.1161/circulationaha.116.021511
|View full text |Cite
|
Sign up to set email alerts
|

Longer Duration and Earlier Age of Onset of Paternal Betel Chewing and Smoking Increase Metabolic Syndrome Risk in Human Offspring, Independently, in a Community-Based Screening Program in Taiwan

Abstract: Original research article BACKGROUND: Transgenerational effects of paternal Areca catechu nut chewing on offspring metabolic syndrome (MetS) risk in humans, on obesity and diabetes mellitus experimentally, and of paternal smoking on offspring obesity, are reported, likely attributable to genetic and epigenetic effects previously reported in betel-associated disease. We aimed to determine the effects of paternal smoking, and betel chewing, on the risks of early MetS in human offspring. METHODS:The 13 179 parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28]. Paternal programming has been likewise described in clinical observation studies [41, 42]. So far most of the animal studies dealing with paternal programming used paternal high-fat diet models prior to mating to investigate potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28]. Paternal programming has been likewise described in clinical observation studies [41, 42]. So far most of the animal studies dealing with paternal programming used paternal high-fat diet models prior to mating to investigate potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Rodgers et al (2013) concluded that “male exposure to stress, either throughout puberty, or in adulthood, reprograms paternal germ cells and results in transmission of an offspring HPA stress axis dysregulation phenotype”. Support for a cumulative effect comes from a study of pre-fatherhood betel chewing and offspring metabolic syndrome (Yen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…MetS is defined as the presence of three or more of the following five risk factors established by the National Cholesterol Education Program-Adult Treatment panel III [ 38 ] based on abdominal obesity criteria for Asian-specific from the International Diabetes Foundation [ 39 ]: (1) abdominal obesity (WC ≥80 cm in women); (2) hypertriglyceridemia (triglycerides, TG ≥150 mg/dL); (3) low level of high-density lipoprotein, HDL cholesterol (<50 mg/dL in women); (4) high blood pressure (systolic BP ≥130 mmHg and/or diastolic BP ≥85 mmHg); (5) high fasting plasma glucose (≥100 mg/dL). In this study, participants with more than 3 of the above-mentioned risk factors of metabolic syndrome were classified into the MetS group and participants with 0 risk factor were classified as the normal group.…”
Section: Methodsmentioning
confidence: 99%